2013
DOI: 10.1159/000345853
|View full text |Cite
|
Sign up to set email alerts
|

The Cross River Gorillas (Gorilla gorilla diehli) at Mawambi Hills, South-West Cameroon: Habitat Suitability and Vulnerability to Anthropogenic Disturbance

Abstract: Only about 300 individuals of the Cross River gorilla (CRG; Gorilla gorilla diehli) survive today. The subspecies is endemic to approximately 12–14 sites at the Cameroon-Nigeria border, and is critically endangered. To understand survival prospects of the CRG at Mawambi Hills, Cameroon, a maximum entropy (MaxEnt) distribution model was used to predict the distribution of gorillas. Overall, 24% of the study area was predicted to be suitable for gorillas. The most important predictors of gorilla distribution wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…This indicates that elevation may be a good determinant for the choice of a nesting site by chimpanzees, where the areas with intermediate values of elevation are more suitable. In contrast, Etiendem, Funwi‐Gabga, Tagg, Hens, and Indah (2013) found that elevation was an important predictor of the Cross River gorilla distribution at Mawambi Hills.…”
Section: Discussionmentioning
confidence: 94%
“…This indicates that elevation may be a good determinant for the choice of a nesting site by chimpanzees, where the areas with intermediate values of elevation are more suitable. In contrast, Etiendem, Funwi‐Gabga, Tagg, Hens, and Indah (2013) found that elevation was an important predictor of the Cross River gorilla distribution at Mawambi Hills.…”
Section: Discussionmentioning
confidence: 94%
“…Agents were assigned predetermined distances from their village of origin which they had to reach before returning home. These distances were randomly chosen from a normal distribution with a mean of zero and a standard deviation of 10 km, chosen because in the study area most of the human activity originating from villages happens within c. 10 km (Etiendem et al 2013;Imong et al 2014a). When agents on their way home reached within three cells of their village of origin (540 m, roughly corresponding to the median radius of settlements in the study area) they changed their direction after a new distance to be reached was randomly chosen as above.…”
Section: Datamentioning
confidence: 99%
“…The less numerous subspecies -and in fact the least numerous gorilla subspecies -is the Cross River gorilla (Gorilla gorilla diehli) found at the Nigeria/Cameroon border and listed as Critically Endangered by the IUCN Red List (2014.2). There are approximately 250-300 individuals living, however, these are distributed in 12-14 small and fragmented populations (Etiendem et al, 2013). The most pressing threats are the destruction or modification of habitat resulting in further isolation of small populations and hunting for the bushmeat and pet trade.…”
Section: Gorillas Under Threatmentioning
confidence: 99%